2016
DOI: 10.1063/1.4962431
|View full text |Cite
|
Sign up to set email alerts
|

Growth of (111)-oriented epitaxial and textured ferroelectric Y-doped HfO2 films for downscaled devices

Abstract: In this study, the growth of (111)-oriented epitaxial and textured YO1.5-HfO2 (0.07:0.93 ratio) films using the pulsed laser deposition method is presented. Epitaxial films were prepared on ITO//(111)yttria-stabilized zirconia (YSZ) substrates (ITO: Sn-doped In2O3; YSZ: yttria-stabilized zirconia), while textured films were prepared on (111)Pt/TiOx/SiO2//Si substrates with and without an ITO buffer layer via the grain on grain coherent growth. Inserting an ITO layer increased the volume fraction of the ferroel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 15 publications
1
45
0
1
Order By: Relevance
“…Further experiments confirmed that YHO films grown on (001) YSZ contain four types of orientations: o 1 , o 2 , o 3 , o 4 , whereas films grown on (100) ITO/(100) YSZ contain two types of orientations: o 5 and o 6 . [74] In addition, Yoong et al [56] studied the growth of epitaxial HZO thin films on [74] 700 0.013 9 --YHO/(001)ITO/(001)YSZ [74] YHO/(110)ITO/(110)YSZ [34] 700 0.013 15 16 Yes YHO/(ITO)/(111)YSZ [136] 700 0.013 14 10 -YHO/YSZ [50] 700 0.013 20 --HZO/(0001)GaN/(111)Si [76] 750 0.1 5.83 --YHO/ITO/YSZ [33,35,137] a) 0.013 10-115 25 No YHO/YSZ/(001)Si [77] 700 0.2 20 -HZO/TiN/(001)YSZ [138] 700 2.6*10 À8 15 7-30 -HZO/TiN/(011)YSZ [138] HZO/TiN/(111)YSZ [138] HZO/LSMO/(001)LAO [56] 550 0.13 10 20 Yes…”
Section: Substrate And/or Bottom Electrode Selectionmentioning
confidence: 99%
“…Further experiments confirmed that YHO films grown on (001) YSZ contain four types of orientations: o 1 , o 2 , o 3 , o 4 , whereas films grown on (100) ITO/(100) YSZ contain two types of orientations: o 5 and o 6 . [74] In addition, Yoong et al [56] studied the growth of epitaxial HZO thin films on [74] 700 0.013 9 --YHO/(001)ITO/(001)YSZ [74] YHO/(110)ITO/(110)YSZ [34] 700 0.013 15 16 Yes YHO/(ITO)/(111)YSZ [136] 700 0.013 14 10 -YHO/YSZ [50] 700 0.013 20 --HZO/(0001)GaN/(111)Si [76] 750 0.1 5.83 --YHO/ITO/YSZ [33,35,137] a) 0.013 10-115 25 No YHO/YSZ/(001)Si [77] 700 0.2 20 -HZO/TiN/(001)YSZ [138] 700 2.6*10 À8 15 7-30 -HZO/TiN/(011)YSZ [138] HZO/TiN/(111)YSZ [138] HZO/LSMO/(001)LAO [56] 550 0.13 10 20 Yes…”
Section: Substrate And/or Bottom Electrode Selectionmentioning
confidence: 99%
“…3,[6][7][8][9][10][11][12][13] The ferroelectric orthorhombic phase can be also stabilized in epitaxial films. [14][15][16][17][18][19][20][21] In epitaxial films, the orthorhombic phase is generally formed during deposition at high temperature, without need of annealing. [14][15][16][17][18][19][20] Epitaxial films are of high interest for better understanding of the properties of ferroelectric hafnia, as well as for prototyping devices with ultrathin films or having small lateral size, for which the higher homogeneity of epitaxial films respect to polycrystalline films is an advantage.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Epitaxial films are of high interest for better understanding of the properties of ferroelectric hafnia, as well as for prototyping devices with ultrathin films or having small lateral size, for which the higher homogeneity of epitaxial films respect to polycrystalline films is an advantage. In spite of the evident interest, epitaxial ferroelectric hafnia is still in a nascent state, and few groups have reported epitaxial films on YSZ, [14][15][16]21,22 oxide perovskite, 17,19,23 and Si 18,20 substrates. Up to now, the epitaxial films have been grown by pulsed laser deposition (PLD), and only the influence of thickness has been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…15),17) However, (100)-oriented films tend to be affected by domain structure destabilizing ferroelectric properties. 18), 19) To obtain stable ferroelectric properties, using (111)-oriented films is a realistic solution employed for current ferroelectric random access memories with Pb(Zr,Ti)O 3 films. In this study, we investigate the effects of substrates, buffer layers, compositions and thicknesses on the constituent phase with respect to (111)-oriented YO 1.5 -substituted HfO 2 and investigate the condition for growing orthorhombic HfO 2 films.…”
Section: Introductionmentioning
confidence: 99%